PROGRAM LAYANAN BIMBINGAN KONSELING PRIBADI SOSIAL UNTUK MENINGKATKAN DAYA JUANG SISWA - YOSEP SETIAWAN (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2019)
Educational institution is an institution of the brain industry. Therefore, education is a vehicle for mental exercise. With education will be able to sharpen the brain to form human beings quality. Qualified people are intelligent human beings comprehensive and competitive savvy are reflected in personal moral, creative, and productive and full responsibility in living our daily lives. But the spotlight and complaints against educational institutions still occur, various perceived problems among students learn the lower interest. Students tend to subjects who tested nationally (National Examination), the methods used by teachers in teaching the more commonly used methods of lecture and question and answer, sometimes the discussion so that the lessons seem monotonous and less innovative, subjects received more students cederung nature doctrine in the form of memorization alone and rarely developed in the context of everyday life so that lessons just more leads to mastery of concepts and tend to train cognitive abilities-intellectual, not a lot of touching the realm of other intelligence in accordance with the potential of the students. The other problem is the tendency of the still rampant behavior is not commendable at this time in various forms, for example, students commit suicide because they do not pass the exam, involved in drugs, fighting between students, the behavior of cheating, careless, style punky, smoking, going out, and so become a reason for choosing this topic as study materials. The problem is what strengthens the belief writers to examine and assess the importance of the development of multiple intelligence through integrative learning-based game in an attempt to develop students' potential intelligence to realize a comprehensive and intelligent smart students competitive. This paper formulated into some discussion that begins with an introduction that lists reasons for the importance of this issue is discussed, and then forwarded to the review of the concept of multiple intelligence. Followed by a study on the definition, purpose and benefits of the games, the development of multiple intelligence through integrative learning-based games and ending with examples of games in integrative learning process.